A Laser‐Processed Silicon Solar Cell with Photovoltaic Efficiency in the Infrared. Issue 7 (3rd February 2021) - Sánchez, Maria Isabel; Delaporte, Philippe; Spiegel, Yohann; Franta, Ben; Mazur, Eric; Sarnet, Thierry
Abstract : Hyperdoped and textured silicon created with a femtosecond laser in the presence of SF6 gas has a highly absorbing surface with extended spectral sensitivity in the infrared. The main drawback of this micro‐ and nanostructured material for photovoltaic (PV) cells is an increase in charge‐carrier recombination at the surface due to the typically poor crystallinity of the surface layer. Laser annealing postprocessing of the black silicon (b‐Si) surface is used to greatly reduce the crystal structure defects while maintaining sub‐bandgap absorption. The back side of the cell is functionalized with spin‐on doping and laser fired contacts to make an interdigitated back‐contact proof‐of‐concept b‐Si solar cell. It is shown that this cell has measurable PV efficiency in the sub‐bandgap infrared, a promising step toward developing intermediate‐band silicon PVs. Abstract : SEM image of a black silicon (b‐Si) with different policristaline structures which are sources of recombination and reduces the efficiency in photoelectrical performance. This article reports a proof‐of‐concept silicon solar cell that has a measurable sub‐bandgap photovoltaic (PV) efficiency in the infrared by improving the crystallinity of the amorphous and polycrystalline surface induced in the b‐Si fabrication.